PEMBANGUNAN DESA BERKESINAMBUNGAN: PENGARUH DANA DESA, KUALITAS PEMBANGUNAN MANUSIA, DAN LUAS WILAYAH TERHADAP PEREKONOMIAN DAERAH DAN PEMBANGUNAN DESA - Rokhmat Taufiq Hidayat; Taufiq Hidayat, Rokhmat; Hadiwibowo, Yuniarto (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2023)
This research analyzes the effects of village funds, quality of human development, and area size on village development with the regional economy as a mediating variable. This research uses Regional Original Income and regional wealth as control variables. Village development is a manifestation of the approach to developing Indonesia from the periphery. The research population is regencies/cities that have village areas, totaling 434 regencies/cities throughout Indonesia. The period analyzed is between 2018 and 2021. Panel data analysis is used to estimate the relationship between variables. The models used are the Common Effects Model (CEM), Fixed Effects Model (FEM), Random Effects Model (REM), and Generalized Estimating Equation (GEE). The results of this research prove that funding for villages and the quality of human resources have a positive effect on village development, while area size is a burden for village development.